Electrogenerative Process For The Recovery Of Gold From Cyanide Solutions And The Formation Of Gold Microstructures On Carbon-Based Matrices - Yap , Chin Yean (2010)
The application of an electrogenerative system as an alternative to the electrochemical recovery of gold from aqueous solutions is presented. This process does not require an external supply of energy due to the spontaneous chemical reaction that takes place in the reactor while generating an external flow of current as a by-product. Two types of operation modes were investigated. A batch reactor operating in an electrogenerative mode is used in gold recovery from cyanide solutions. In this study, gold cyanide solutions serve as the catholyte because cyanide is the most common leachant used during the extraction of metals in the hydrometallurgical industry. The batch reactor with an improved design using three dimensional cathodes namely porous graphite and reticulated vitreous carbon (RVC) and two dimensional cathode materials, copper and stainless steel plates were coupled with a zinc anode. The system resulted in more than 90% gold being recovered within 3 h of operation. Activated RVC serves as a superior cathode material having the highest recovery rate with more than 99% of gold being recovered in 1 h of operation. An electrogenerative flow-through reactor with an activated RVC cathode was also developed. The reactor proved to be efficient in recovering more than 99% of gold within 4 h of operation. The performance of the reactor was evaluated with initial KAu(CN)2 concentrations of 0.051 mM, 0.508 mM , 2.54 mM and various electrolyte flow rates. Gold recovery was found to be strongly dependent on electrolyte flow rate and initial gold concentration in the cyanide solution under the experimental conditions used.